PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI PENDEKATAN WHOLE LANGUAGE - -, FAHRURROZI (Jurnal Pendidikan Usia Dini, 2017)
The purpose of this study was to obtain empirical data about the increased ability of one grade student’ reading at SDN Kramat Pela 07 Pagi Jakarta Selatan, using the whole language. The research was conducted at SDN Kramat Pela 07 Pagi Jakarta Selatan to the subject of research is the one grade students, amounting 30 studens in the first semester of academic year 2014/2015. Classroom action research was conducted using a cycle of John Elliot. Classroom action research conducted through the stages of planning, implementation actions, monitoring/observation, of reflection and evaluation as a basis for re-planning of each subsequent cycle. The research was carried out as much as 2 cycles where each cycle consists of 3 x meetings with each meeting time allocation of 2 x 35 minutes. The results obtained from student evaluations at each cycle are as follows : I cycle 53 % of students who have reached the score of 75, whereas in cycle 2 there was an increase to 100 % of students who have reached the score of 75. The implications of this research is the use of whole language can be one of alternative menthods to improve student’ reading grade I at SDN Kramat Pela 07 Pagi Jakarta Selatan. Keywords : reading ability and whole language